Multisensory Brand Experiences in Digital Media - Thomas Heinrich Musiolik; Kasun Karunanayaka; Adrian David Cheok (Marketing Review St.Gallen, 2019)
Sensations based on touch, taste, and smell can add new dimensions to the digital experience. This article discusses why a multisensory approach will in future be necessary for marketing brands in digital media and provides a short overview of the multisensory processing of the brain and the latest trends in multisensory technologies.
Keywords: 650